The Relationship between ES-QUAL Model and Online Purchase Intention in the Context of Rising Global Marketplace of E-Commerce - Sana Baqai; Jawaid Ahmed Qureshi; Ejindu Iwelu MacDonald Morah (Faculty of Economic and Business, 2021)
The electronic service quality (ES-QUAL) of the e-commerce service providers plays a central role. The primary purpose of this paper is to investigate the effect of the ES-QUAL model's four dimensions (efficiency, fulfillment, privacy, and system availability) on purchase intention and examine ES-QUAL's relationship with electronic word-of-mouth (EWOM), brand image, and purchase intention. This research uses Structural Equation Modeling (SEM) for empirical analysis. Results show ES-QUAL model positively and significantly impacts purchase intention, and the effect of the ES-QUAL model relatively increases when mediated by electronic word of mouth (EWOM) and brand image. This research provides insights to E-marketers, entrepreneurs, and e-commerce players to improve online consumers' purchase intention, sales, and services. Practitioners can gain customers' attention by enhancing the quality of their websites and by assuring efficiency, privacy, system availability, and fulfilling their promise about delivering products. They also need to consider EWOM and brand image, as both positively impact online purchase intention, which can lead to the overall sustainable development of an organization.JEL Classification: M31, L81How to Cite:Baqai, S., Qureshi, J. A., & Morah, E. I. M. (2021). The Relationship Between ES-QUAL Model and Online Purchase Intention in the Context of Rising Global Marketplace of E-Commerce. Etikonomi, 20(2), xx– xx. https://doi.org/10.15408/etk.v20i2.20677.